Hard-rock TBM jamming subject to adverse geological conditions: Influencing factor, hazard mode and a case study of Gaoligongshan Tunnel - Xu, Z.H.; Wang, W.Y.; Lin, P.; Nie, L.C.; Wu, J.; Li, Z.M. (Tunnelling and underground space technology, 2021)
•Influencing factors of TBM jamming were statistically investigated.•Hazard modes of TBM jamming were proposed.•Countermeasures for TBM jamming were developed. Adverse geological conditions, the major challenge of tunnel construction, affect the excavation rate and even cause the hard-rock tunnel boring machine (TBM) jamming. Firstly, 121 cases of TBM jamming are analyzed in this study (detailed information can be found in Appendix A). The influencing factors of TBM jamming are studied and the hazard modes are classified into six categories. The selection of shield TBM takes up 77.69% of the 121 cases, occurring in 94 cases. In terms of adverse geological conditions, the fractured zone is one of the most commonly met adverse geological conditions for TBM jamming cases. In addition, groundwater often plays an indirect catalytic role in jamming hazards. It is found that collapse of surrounding rocks is the most common hazard mode for TBM jamming, appearing in 52 cases. Secondly, Gaoligongshan Tunnel, one of the longest railway tunnels in China, is presented as a representative case. The possibility, geological conditions and locations of TBM jamming occurring in the Gaoligongshan Tunnel are studied in site, which verifies the results of case statistics and the geological laws proposed above. The specific steps to predict and control TBM jamming in Gaoligongshan Tunnel are proposed. Finally, the lessons learned are summarized, and the countermeasures for TBM jamming are developed regarding three stages of TBM tunnel construction. The results of this study provide a reference for the mechanism of TBM jamming and share certain practical countermeasures to ensure a safe and efficient TBM excavation in adverse geological conditions.